Harmonisasi Hukum Adat dan Hukum Positif di Indonesia - Meha Middlyne Simbolon (CV Rewang Rencang, 2025)
Customary law plays a significant role in land management in Indonesia, including the recognition of girik as proof of land ownership. Girik is one of the documents acknowledging land ownership in Indonesia, recognized within the customary legal system. However, over time, the dualism between customary law and positive law has created various issues, ranging from ownership legality to agrarian conflicts. This study explores how customary law influences the existence of girik, the problems arising from legal dualism, and solutions for harmonizing the two systems. Using a descriptive-analytical approach, the study finds that customary law offers effective conflict resolution mechanisms at the local level, yet these are often overlooked within the formal legal system.